Batter biscuits on the basis of oat malt with high biological value - Skrypko, Anhelina; Obolkina, Vera; Yemelyanova, Nina; Kyianytsia, Svetlana (My University, 2013)
Improving technology butter cookie with a high content of essential amino acids, macro-and micronutrients and other bioactive components. Adding malt flour contribute to the accumulation of maltose and glucose through hydrolysis of starch under the action of amylolytic enzymes, which can reduce the sugar content in pastry products.
Keywords: wheat flour; malt flour; unfermented flour with oat malt; oat meal; борошно пшеничне; солодове борошно; борошно з неферментованого вівсяного солоду; вівсяне борошно; кафедра технології хлібопекарських і кондитерських виробів